Human endogenous retroviruses and chosen disease parameters in morphea - Kowalczyk, Michał J.; Dańczak-Pazdrowska, Aleksandra; Szramka-Pawlak, Beata; Żaba, Ryszard; Osmola-Mańkowska, Agnieszka; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Morphea (localized scleroderma) is a relatively rare disease characterized by excessive skin fibrosis. Human endogenous retroviruses (HERV) are largely distributed within the human genome with hundreds of thousands of elements. The HERV have been widely studied in autoimmune disorders, yet hardly ever assessed in diseases with a good prognosis such as morphea. Aim: In this study we focus on the possible relations between the expression of chosen HERV and factors influencing the pathomechanism of the disease, such as age, sex, titres of anti-nuclear antibodies, as well as duration, activity, and severity of the disease (LoSSI index). Material and methods: Real-time polymerase chain reaction (PCR) targeting six HERV sequences of interest were performed on samples derived from peripheral blood mononuclear cells (PBMC) and skin biopsies. Results: In PBMC we found a statistically significant negative correlation between HERV-W env expression and LoSSI index (p = 0.01). Additionally, HERV-W env was downregulated in patients with the active form of morphea. In all other cases we found no correlation whatsoever nor statistically significant differences below the p = 0.05 threshold. Conclusions : Morphea seems to be an autoimmune disease where the impact of HERV is not so apparent. It seems that probing many patients for the expression of just a few sequences is not as effective as previously expected. For initial studies of HERV in other diseases we recommend high throughput techniques such as HERV-dedicated DNA microarrays or massive parallel sequencing.